Acoustic characteristics of the Latvian diphthongs produced by male and female informants - Grigorjevs, Juris (Baltistica, 2016)
The aim of the present study was finding acoustic characteristics of the Latvian diphthongs irrespective of the speaker’s gender. The method designed by the author allowed to compare diphthongs of different duration, thus revealing common tendencies both in the formant structures and in the diphthong paths on the vowel plane. A comparison of the diphthong paths with the location of the long monophthongs on psychophysical F2′ vs. F1 plane showed that the paths begin in the vicinity of the corresponding monophthong but end with an undershoot, i.e., not completely reaching the target frequencies. Dynamics of the formant trajectories of the Latvian diphthongs produced in the zero context in most cases display a two-phase pattern with a relatively short steady state of the first component (the longest in [ie] and [uo]: about 1/3 of the total duration) and a long transitionary phase with no steady state of the second component. The duration of the Latvian diphthongs (W) is between that of the short (V) and the long (Vː) monophthongs. The durational ratio of the short monophthongs to the diphthongs and the long monophthongs is V : W : Vː = 1 : 1.5 : 2.